Environmental impacts of infrastructure development under the Belt and Road Initiative - Teo, Hoong Chen; Lechner, Alex Mark; Walton, Grant W.; Chan, Faith Ka Shun; Cheshmehzangi, Ali; Tan-Mullins, May; Chan, Hing Kai; Sternberg, Troy; Campos-Arceiz, Ahimsa (2019)
China’s Belt and Road Initiative (BRI) is the largest infrastructure scheme in our lifetime, bringing unprecedented geopolitical and economic shifts far larger than previous rising powers. Concerns about its environmental impacts are legitimate and threaten to thwart China’s ambitions, especially since there is little precedent for analysing and planning for environmental impacts of massive infrastructure development at the scale of BRI. In this paper, we review infrastructure development under BRI to characterise the nature and types of environmental impacts and demonstrate how social, economic and political factors can shape these impacts. We first address the ambiguity around how BRI is defined. Then we describe our interdisciplinary framework for considering the nature of its environmental impacts, showing how impacts interact and aggregate across multiple spatiotemporal scales creating cumulative impacts. We also propose a typology of BRI infrastructure, and describe how economic and socio-political drivers influence BRI infrastructure and the nature of its environmental impacts. Increasingly, environmental policies associated with BRI are being designed and implemented, although there are concerns about how these will translate effectively into practice. Planning and addressing environmental issues associated with the BRI is immensely complex and multi-scaled. Understanding BRI and its environment impacts is the first step for China and countries along the routes to ensure the assumed positive socio-economic impacts associated with BRI are sustainable.